PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT APS - Maesaroh, Siti; Anggraini, Melina; Waruru, Hatoli (LPPM UNIVERSITAS INSAN PEMBANGUNAN INDONESIA, 2023)
The role of good leadership tends to diminish, likewise with employee motivation which influences low employee performance. A decrease in employee performance has a significant impact on employee work results. This condition affects the profits generated by the company. If this happens continuously, of course, there will be a deficit that the company will experience. This research aims to determine the influence of leadership style on employee performance, the influence of work motivation on employee performance, to determine the influence of leadership style and work motivation on employee performance. The results of the coefficient of determination test or R square value are 0.726, so it can be concluded that leadership style and work motivation have a strong influence on employee performance. The results of hypothesis testing regarding the influence of leadership style on employee performance resulted in the t-count of leadership style being 2.508 > 1.998 so it can be concluded that there is a significant influence between leadership style on employee performance. The influence of work motivation on employee performance results in a t-count of work motivation of 2.878 > 1.998 so it can be concluded that there is a significant influence between work motivation and employee performance. The hypothesis test (F test) produces F - count > F - table, namely 5.133 > 2.36. This means that there is a significant simultaneous influence between the variables of leadership style and work motivation on employee performance. Keywords: Leadership Style, Motivation, and Employee Performance.